PENGARUH WORD OF MOUTH DAN LOKASI TERHADAP KEPUTUSAN MENGAMBIL KREDIT DI LEMBAGA PERKREDITAN DESA “MARTO NUGROHO” DESA ROWOMARTO KECAMATAN PATIANROWO KABUPATEN NGANJUK - Dhiyan Septa Wihara (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2019)
This study aims to 1) Analyze the effect of word of mouth on credit decision making at the institution of village credit "marto nugroho" rowomarto village patianrowo sub-district nganjuk regency, 2) Analyze the influence of location on credit decision making at the village credit institution "marto nugroho" rowomarto village patianrowo district nganjuk, 3) analyze word of mouth and location for decision to take credit at the village credit institution "marto nugroho" rowomarto village, patianrowo sub-district nganjuk district. The population in this study were all active and non-active rural credit institutions "marto nugroho which numbered 150 people. The number of samples used was 60 respondents with sample determination techniques using Slovin formula. retrieval of data using questionnaires. Data analysis techniques using multiple linear regression analysis with t test to analyze the influence of partial and F test to analyze simultaneous influence. Based on the analysis it was found that the significant level of the F test was 0,000 (p <0.05), this means that word of mouth and location had a significant effect on the decision to take credit in the village credit institution "Marto Nugroho" rowomarto village in Patianrowo sub-district Nganjuk district. On the other hand based on the results of the t test it can be seen that partially word of mouth has a significant effect on the decision to take credit in the village credit institution "marto nugroho" rowomarto village in the district of Patianrowo district, the significance is 0,000 (p <0.05). While the location partially also has a significant effect on the decision to take credit in the village credit institution "Marto Nugroho" rowomarto village, Patianrowo sub-district, Nganjuk, with a significance value of t test of 0.000 (p> 0.05). Word of mouth variables are more dominant because the beta value is greater than the location variable which is 0.466